Continence and quality of life with the modified Heitz-Boyer-Hovelacque rectal bladder for children with urinary incontinence following bladder exstrophy. Issue 3 (June 2016) - Messina, M.; Molinaro, F.; Ferrara, F.; Angotti, R.; Bulotta, A.L.; Di Maggio, G.; Bianchi, A.
Summary: Background: Bladder exstrophy and epispadias are severe congenital anomalies associated with an open bladder and urinary sphincter. Despite modern reconstruction, there is a significant incidence of residual or recurrent urinary incontinence that impacts on quality of life (QoL) and self-esteem, which in turn limits social interaction (Figure). The present study involved 14 patients, mainly from a Middle Eastern country, and reported the early findings with a modification of the Heitz-Boyer-Hovelacque rectal bladder technique for both urinary and faecal control. Study design: Fourteen children, with a median age of 8.1 years, with poor quality of life and low self-esteem because of urinary incontinence and small polypoidal open bladders of 5–15 ml volume, mostly after bladder exstrophy surgery, were managed with a modification of the Heitz-Boyer-Hovelacque rectal bladder technique keeping an intact anal sphincter. The retrorectal pulled-through colon was anastomosed to the posterior wall of the rectum just above the external sphincter complex, thereby avoiding any possible injury to the anal sphincter. All patients had a normal colon and a competent anal sphincter without lumbosacral spinal or nerve anomalies. Results: Ten children had a 5- to 10-year follow-up, one child had a 15-year follow-up, and three others, that were also continent, were excluded because of a <5-year follow-up. There were no postoperative complications, and all were dry and odour-free by day within 2–4 weeks of surgery. Two children still had minor urinary loss at night. There were no UTIs and renal function remained unimpaired. Eleven years after surgery, one child underwent excision of a pedunculated benign inflammatory polyp from the tip of the left ureter because of recurrent torsion and bleeding, there was no recurrence at the 2-year follow-up. None of the rectal or ureteric biopsies from any of the children showed metaplasia or neoplasia; however, in view of the potential long-term risks, all children were placed on a lifelong 'proctoscopy and biopsy' protocol. Discussion: The ability to be dry and odour-free, and to wear normal clothing had a striking impact on QoL and psychological well-being of the children and their families. This was reflected in their positive overall approach, voluntary school attendance, and enthusiastic participation in communal events. All agreed that their improved genital appearance markedly contributed to their better body image and increased self-esteem. Conclusion: These significant benefits, at a crucial time in the child's life, outweigh the potential risk of long-term neoplasia. Therefore, the Heitz-Boyer-Hovelacque rectal bladder technique is recommended with long-term proctoscopic follow-up. Figure Female (A) and male (B) anatomy after failed reconstruction.